Fabrication and characterization of a novel herbicide delivery system with magnetic collectability and Its phytotoxic effect on photosystem II of aquatic macrophyte - Forini, Mariana Monteiro de Lima; Antunes, Débora Ribeiro; Cavalcante, Luiz Aparecido Ferreira; Pontes, Montcharles da Silva; Biscalchim, Érica Rennó; Sanches, Alex Otavio; Santiago, Etevaldo Felipe; Fraceto, Leonardo Fernandes [UNESP]; Grillo, Renato [UNESP] (American Chemical Society (ACS), 2020)
The use of nano- and microparticles as a release system for agrochemicals has been increasing in agricultural sector. However, the production of eco-friendly and smart carriers that can be easily handled in the environment is still a challenge for this technology. In this context, we have developed a biodegradable release system for the herbicide atrazine with magnetic properties. Herein, we investigated the (a) physicochemical properties of the atrazine-loaded magnetic poly(ε-caprolactone) microparticles (MPs:ATZ), (b) in vitro release kinetic profile of the herbicide, and (c) phytotoxicity toward photosynthesis in the aquatic fern Azolla caroliniana. The encapsulation efficiency of the herbicide in the MPs:ATZ was ca. 69%, yielding spherical microparticles with a diameter of ca. 100 μm, a sustained-release profile, and easily manipulated with an external magnetic field. Also, phytotoxicity issues showed that the MPs:ATZ maintained their herbicidal activity via inhibition of PSII, showing lower toxicity compared with the nonencapsulated ATZ at 0.01 and 0.02 μmol·L–1. Therefore, this technology may conveniently promote a novel magnetic controlled release of the herbicide ATZ (with the potential to be collected from a watercourse) and act as a nutrient boost to the nontarget plant, with good herbicidal activity and reduced risk to the environment.
Keywords: Microparticles; Controlled release; Magnetic NPs; Atrazine; Azolla caroliniana